New trends for the economic development of the Northeast - de Mattos, Fernando Augusto Mansor; Martignoni, Enrico Moreira (Revista Econômica do Nordeste, 2016)
This paper compares the performance of some selected economic activities in the Northeast with the whole country and analyzes characteristics of the increasing formalization of the region’s labor market. The main data source used is the PNADs (National Research by Household Sample), whose micro-data were organized and manipulated to provide the information about the desired data. Data from the IBGE industrial researches were also used. Basically, the method of analysis consists in comparing the evolution of some product and employment indicators in the Northeast region with the national average. Subsequently, we assessed the main changes in the income and occupation structures in the Northeast region for the period up to 2008. The study concludes that the grounds have been laid for the installation of sustained economic development in the region. We further warn, however, about the need to maintain this pace of development of the national economy and that the Brazilian government should continue to consider regional issues. We also warn about the uncertainties regarding the continual domestic growth rate in the face of international instability and the risk of deindustrializacion. Still, our results admit the outlook for improved regional income distribution in Brazil.